1986
DOI: 10.1111/j.1365-2885.1986.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and pharmacokinetics of phenylbutazone in Welsh Mountain ponies

Abstract: The disposition of phenylbutazone (4.4 mg/kg), administered intravenously to six Welsh Mountain ponies, was described by a two-compartment open model. Pharmacokinetic parameters were not significantly different after morning dosing in comparison with afternoon dosing. When phenylbutazone (4.4 mg/kg) was administered orally to the same ponies, marked variations in time to peak concentrations were produced with different feeding schedules. When access to hay was permitted before and after dosing, the mean time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 13 publications
6
52
0
Order By: Relevance
“…In contrast, for some NSAIDs that bind to cellulose, absorption is delayed for several hours and likely is in the distal segment of the digestive tract. 3 Meloxicam is intended for repeated administrations. The study reported here documented that with respect to F, there was no significant difference between the first and last oral administrations and that the data fit a bicompartmental model well, which is consistent with the hypothesis that meloxicam disposition (absorption, distribution, and elimination) is independent of time and dose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, for some NSAIDs that bind to cellulose, absorption is delayed for several hours and likely is in the distal segment of the digestive tract. 3 Meloxicam is intended for repeated administrations. The study reported here documented that with respect to F, there was no significant difference between the first and last oral administrations and that the data fit a bicompartmental model well, which is consistent with the hypothesis that meloxicam disposition (absorption, distribution, and elimination) is independent of time and dose.…”
Section: Discussionmentioning
confidence: 99%
“…5,r Feeding conditions of horses can influence the plasma concentration patterns of several NSAIDs. 3,11 Therefore, the influence of the feeding conditions on meloxicam disposition was investigated by use of 2 feeding regimens (fed and nonfed). The study reported here documented that the F for the oral route of administration was high for both regimens (85 ± 19% for nonfed horses and 96 ± 13% for fed horses) and not significantly different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSAIDs can cause ulceration throughout the entire gastrointestinal tract of horses [10,13,6]. The exact reason for the localization of ulceration in the right dorsal colon has not been elucidated; however, one hypothesis is that phenylbutazone is bound extensively to roughage and is released after fermentation in the large colon [14]. There is prolonged contact time between the drug and the right dorsal colon due to the slow transit time and the narrowing of the lumen at the junction of the right dorsal colon and the transverse colon [3].…”
Section: Minireview Of the Literaturementioning
confidence: 99%
“…Absorption rate constant, Tmax and apparent elimination rate constant after intraduodenal administration of 20 mg/kg of SDM in pigs. It is well known that the pharmacokinetics after oral administration is unpredictable, especially in practical field conditions, because of fluctuations in the absorption process due to the prandial state and differences in individual gastrointestinal tracts (3,4,6,7,13). The fluctuation of the time course of Cf, possibly due to the change in ka during the experimental period, was also observed in those animals (numbers 2 and 3) which had a relatively small ka value (Figure 2).…”
Section: Discussionmentioning
confidence: 99%